WC-Cu thermal barriers for fusion applications - Dias, Marta (2018)
ABSTRACT: WC-Cu cermets have been devised for thermal barriers between the plasma facing tungsten tiles and the copperbased heat sink in the first wall of nuclear fusion reactors. Composite materials with 50 and 75 v/v% WC have been prepared by hot pressing at 1333 and 1423 K with pressures of 37 and 47 MPa, respectively. Microstructural changes have been investigated by scanning electron microscopy coupled with energy dispersive X-ray spectroscopy and X-ray diffraction. The materials consolidated have also been evaluated in terms of Archimedes' density, thermal diffusivity, Vickers hardness and elastic modulus. Implantation was carried out at room temperature with Ar+ at 100 keV ion beam with a fluence of 4 · 1020 at/m2. The materials consisted of homogeneous dispersions of WC particles in a Cu matrix and presented densifications of about 90%. Incipient swelling in copper-rich regions have been observed on the implanted surfaces, however no significant changes have been detected by X-ray diffraction. Higher WC content in the cermet materials increased hardness and the elastic modulus. The cermets' thermal diffusivity was significantly lower than that of pure copper or tungsten, as desirable for a thermal barrier.